Purchasing Behaviour of Generation Z within Cosmetics Industry in the Czech Market - Medková, Veronika (2024)
The aim of this study is to identify the main drivers influencing the purchasing behaviour of Generation Z when buying sustainable personal care cosmetic products in order to extract pertinent insights, allowing for the formulation of strategic implications in marketing that effectively appeal to and attract a larger customer base within this specific demographic. The research was conducted through an online questionnaire survey between Czech respondents (N = 164), which covered inquiries into the factors influencing purchasing behaviour, values prevalent within this generation, price perception, significance of packaging, and communication channels in the cosmetics industry. Following data collection, descriptive statistics was employed to summarize the survey responses, clarifying the fundamental characteristics of the dataset. Additionally, Spearman's correlation test was conducted to explore the relationships between various factors influencing purchasing behaviour. Specifically, this test examined the associations between the aforementioned variables of interest and their relevance to the research objectives, thereby offering insights into the interplay among these factors in shaping consumer behaviour within the cosmetics sector. The results show that the main drivers of purchasing behaviour of Generation Z in the Czech Republic are sustainable values, environmental awareness and green trust.